Time of acquisition of HCV infection in renal transplant recipients: a major prognostic factor for disease progression - Delladetsima, I.; Psichogiou, M; Sypsa, V; Sakellariou, S.; Hatzakis, A; N. Boletis J (Clin TransplantClin TransplantClin Transplant, 2013)
BACKGROUND: This study aims to identify crucial factors affecting the evolution of liver disease in HCV-infected renal transplant recipients. METHODS: Forty-two HCV-infected recipients with known time of HCV acquisition were followed up for a mean (SD) of 7.6 +/- 3.4 yr after transplantation with consecutive liver biopsies. Hepatitis progression was defined by: a) fibrosis progression >/= 0.2 stages/yr and/or b) development of a cholestatic syndrome. RESULTS: Twenty-three patients (54.8%) displayed benign and 19 (45.2%) aggressive hepatitis progression. Hepatitis course was aggressive in 9.1% and 85% of the patients infected pre- and peri/post-transplantation, respectively (p < 0.001). In multivariate analysis, patients who acquired HCV infection peri- or after transplantation had an increased risk of an adverse outcome compared with those infected before transplantation (p = 0.001). HCV RNA levels at the time of first liver biopsy were lower in patients showing a benign course compared with those with aggressive evolution (p = 0.052). CONCLUSIONS: Time of acquisition of HCV infection is a major prognostic factor for hepatitis progression in the setting of renal transplantation. Immunosuppression was found to be determinant in the progression of HCV infection acquired peri- or post-transplantation. High viral load seems to be crucial in the pathogenetic process.
Keywords: *Postoperative Complications; Adult; Disease Progression; Female; Follow-Up Studies; Graft Rejection/*immunology; Graft Survival/*immunology; Hepacivirus/genetics/*pathogenicity; Hepatitis C/*etiology/pathology; Humans; Kidney Transplantation/*adverse effects; Liver Cirrhosis/*etiology/pathology; Male; Middle Aged; polymerase chain reaction; Prognosis; RNA, Viral/genetics; Time Factors